Theorizing the Americanist Tradition - Valentine, Lisa Philips, 1954-; Darnell, Regna (Book collections on Project MUSE., 1999)
"This collection challenges the prevailing notion that the Americanist Tradition in anthropology, typified by Franz Boas and his colleagues, is atheoretical. Contributions from twenty-five distinguished scholars are brought together here to provide a comprehensive, accessible, state-of-the-art appraisal of interdisciplinary research in the areas of anthropology, linguistics, and Native Studies."--Jacket